Identifying Student Competencies in Sustainable Energy: APreliminary Study of Chemistry Education Students in Indonesia - Bayani, Faizul; Hulyadi, Hulyadi; Pomeistia, Meilynda; Rahman, Rahman (LITPAM, 2026)
This preliminary study identifies the competencies of chemistry education students in understanding sustainable energy within the context of Indonesia’s energy transition. The study addresses a gap in energy education research by examining not only conceptual knowledge but also analytical, contextual, and policy-oriented reasoning across four strategic energy domains: hydrocarbons, hydrogen, bioethanol, and biodiesel. An exploratory descriptive assessment design was employed with undergraduate chemistry education students who had completed Organic Chemistry and Instrumental Chemistry courses. Participants were selected through purposive sampling and completed a four-item essay-based instrument. Student responses were scored using a four-point analytic rubric in which 1 indicated low competence and 4 indicated strong competence; the rubric assessed conceptual accuracy, comparative analysis, contextual relevance, multidimensional evaluation, and policy reasoning. The results showed that the highest mean score was obtained for energy efficiency and environmental impact analysis (M = 3.33), indicating relatively stronger competence in comparing hydrocarbons and hydrogen. Lower mean scores were found for the Indonesian prospects of bioethanol and biodiesel (M = 2.00), comparative evaluation across energy sources (M = 2.33), and sustainable energy policy recommendations (M = 2.00). These findings suggest that students were more prepared for concept-based scientific explanation than for contextual application, synthesis, and strategic policy reasoning. The study provides an initial diagnostic basis for improving sustainable energy education through contextual, interdisciplinary, and problem-based learning linked to Indonesia’s renewable resource potential.